Transformation and overview of audit in past 20 years: a bibliometric analysis - Diamantina Amélia Parckings Tauro Cumbana; José Biléu Ventura (Cogent Business & Management, 2024)
Audit is an important instrument that organizations used to prevent the occurrence of frauds along the years. Investigations in the field of audit are increasing, however, none of them presents quantitative overview on audit-related publications from 2003 to 2023. To fill this gap, this study aims to identify the transformation of audit related research in the past 20 years using bibliometric analysis and suggest avenues for future research in the audit fields. We analyzed a sample of 1177 articles published on Scopus and Web of Science databases. The results show that the most frequent keywords used by the authors were corporate governance, audit quality, audit and audit committee. United States of America (USA), United Kingdom (UK), China are the leader countries in this field. Sustainability, Cogent Business and Management and Current Issues in Auditing, are the most prolific journals. The article shows how audit is a pertinent topic and demands upcoming investigations about. This article makes an important contribution to the current literature on audit through a bibliometric analysis and describe future research and research agenda audit matter for academics.